2011
DOI: 10.1097/mlr.0b013e318202858e
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Clinical Practice Guidelines for Breast and Cervical Cancer Screening

Abstract: Background-Multiple clinical practice guidelines exist for breast and cervical cancer screening, and differ in aggressiveness with respect to the recommended frequency and target populations for screening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
47
0
3

Year Published

2011
2011
2015
2015

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(52 citation statements)
references
References 40 publications
2
47
0
3
Order By: Relevance
“…16 Interestingly, providers in our survey reported that USPSTF guidelines were most influential in their care, in contrast to an earlier nationally representative survey that found the ACS and ACOG guidelines to be most influential. 20 As in prior studies, most providers in our survey valued multiple guidelines. 20 To date, surveys of the cancer screening practices of primary care providers have focused on physicians; [13][14][15]19 our sample included nurse practitioners, certified nurse midwives, and physician assistants, who are becoming more central to the provision of primary care as models of team-based care are disseminated.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…16 Interestingly, providers in our survey reported that USPSTF guidelines were most influential in their care, in contrast to an earlier nationally representative survey that found the ACS and ACOG guidelines to be most influential. 20 As in prior studies, most providers in our survey valued multiple guidelines. 20 To date, surveys of the cancer screening practices of primary care providers have focused on physicians; [13][14][15]19 our sample included nurse practitioners, certified nurse midwives, and physician assistants, who are becoming more central to the provision of primary care as models of team-based care are disseminated.…”
Section: Discussionmentioning
confidence: 61%
“…20 As in prior studies, most providers in our survey valued multiple guidelines. 20 To date, surveys of the cancer screening practices of primary care providers have focused on physicians; [13][14][15]19 our sample included nurse practitioners, certified nurse midwives, and physician assistants, who are becoming more central to the provision of primary care as models of team-based care are disseminated. 21 We examined a broader set of practice characteristics and found that providers who practiced in hospital-based settings were less likely to recommend screening in excess of both guidelines.…”
Section: Discussionmentioning
confidence: 61%
“…A recent survey of primary care physicians (PCPs) found that the influence of screening guidelines varies by specialty (i.e., family practice, internal medicine, or OB/GYN), by the perceived aggressiveness of the recommendations, and by the number and agreement of different guideline recommendations. 20 Among the physicians surveyed, Task Force recommendations were found to be less influential than those issued by the American Cancer Society (ACS) or the American College of Obstetricians and Gynecologists (ACOG).…”
mentioning
confidence: 98%
“…This is one of the reasons why the effectiveness of guidelines as tools to facilitate the translation of evidence into practice has been inconsistent. [20][21][22] The harmonization of guidelines and their integration into an implementation plan represent important first steps in addressing this issue. 23 In this article, we describe the process by which we harmonized recommendations from clinical practice guidelines and implementation tools for the target conditions.…”
Section: Cmaj Openmentioning
confidence: 99%
“…Our findings are consistent with the literature: for a recommendation to be clinically useful, it not only has to have robust evidence, it also has to be formulated in a way that is actionable. [20][21][22][23]28 We disassembled high-quality clinical practice guideline recommendations into their core components and reassembled them into integrated, implementable and measurable recommendations for use in the BETTER trial. We accomplished this using a participatory approach through direct engagement with end-users and researchers, ensuring direct interactivity between the "knowledge creation" process and the "knowledge application" process from the knowledge-toaction cycle, while facilitating greater uptake within the BETTER trial.…”
Section: Cmaj Openmentioning
confidence: 99%